PROBLEM POSING LEARNING (PPL) TO TEACH STUDENTS’ SPEAKING ABILITY - Zulaikah Zulaikah (Pendidikan Bahasa Inggris STKIP Nurul Huda, 2017)
This thesis entitled â€œProblem Posing Learning (PPL) to Teach Studentsâ€™ Speaking Abilityâ€. The problem of this study as follows: â€œIs there any significant difference between the students who are taught by using Problem Posing Learning (PPL) and who are taught by using conventional method at eighth grade students of MTs Nurul Huda Sukaraja OKU Timur?â€ In this study, the writer used true experimental design, where this design consisted of experimental and control group. The population in this study is eighth grade students of MTs Nurul Huda Sukaraja OKU Timur. The number of the population is 125 students. Whereas, in taking the sample, the writer used cluster random sampling. Therefore, class VIII.1 was chosen as experimental group who were taught speaking using Problem Posing Learning (PPL) and class VIII.2 as control group who were taught speaking conventionally. In this study, the writer used the test to collect the data. Based on the findings, it was found that the mean score of pre test in the experimental group was 54.24, and post test score was 70.25. While the mean score of pre test in control group was 53.14, and post test score was 64.2. And the result of analyzing the data, was t-obtained was 2.77 while t-table was 2.046. It means that t-obtained was higher than t-table this indicated that Ho was rejected and consequently Ha was acceptable. It means that Problem Posing Learning (PPL) is effective to apply at eighth grade students of MTs Nurul Huda Sukaraja OKU TIMUR.